If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5w(w + -3)(w + 2) = 0 Reorder the terms: -5w(-3 + w)(w + 2) = 0 Reorder the terms: -5w(-3 + w)(2 + w) = 0 Multiply (-3 + w) * (2 + w) -5w(-3(2 + w) + w(2 + w)) = 0 -5w((2 * -3 + w * -3) + w(2 + w)) = 0 -5w((-6 + -3w) + w(2 + w)) = 0 -5w(-6 + -3w + (2 * w + w * w)) = 0 -5w(-6 + -3w + (2w + w2)) = 0 Combine like terms: -3w + 2w = -1w -5w(-6 + -1w + w2) = 0 (-6 * -5w + -1w * -5w + w2 * -5w) = 0 (30w + 5w2 + -5w3) = 0 Solving 30w + 5w2 + -5w3 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '5w'. 5w(6 + w + -1w2) = 0 Factor a trinomial. 5w((3 + -1w)(2 + w)) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0Subproblem 2
Set the factor '(3 + -1w)' equal to zero and attempt to solve: Simplifying 3 + -1w = 0 Solving 3 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1w = 0 + -3 -1w = 0 + -3 Combine like terms: 0 + -3 = -3 -1w = -3 Divide each side by '-1'. w = 3 Simplifying w = 3Subproblem 3
Set the factor '(2 + w)' equal to zero and attempt to solve: Simplifying 2 + w = 0 Solving 2 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + w = 0 + -2 w = 0 + -2 Combine like terms: 0 + -2 = -2 w = -2 Simplifying w = -2Solution
w = {0, 3, -2}
| -3[r+4]=-21 | | 5[q+6]=-20 | | 5[q+6]=20 | | 8x-9=33-4x | | 5x+7=2x-9 | | -3(-4-6x)=84 | | x^3+2x^2+4=0 | | -y+3z=9 | | 12+18x=84 | | 2+18x=84 | | 6x-6x=-2 | | 3x^3-6x^2-45x=0 | | 7k^2+6k-1=0 | | 5-(3n+5)=3-(7n+3) | | 14m+4n-6m+11n= | | 6n^2-14+8=0 | | 3(u-3)=2(x+5) | | [b+5]=2b+3 | | 15x^2-61x+53=-3 | | -2[5y-1]=-10 | | x^2+5x+62.5=0 | | 4x^2-29x-23=1 | | 2x+5(7)= | | 16x-16=5+x | | 1-6(1+3r)=-113 | | 42x^2+31x-19=2 | | 8x+6=180 | | (25ln(5)-23ln(0))-(25ln(2)-23ln(3))=x | | 5t=1.905 | | 24=23x-15x | | -7a=-385 | | -8-w=11 |